Precursor-Based Earthquake Prediction Research: Proposal for a Paradigm-Shifting Strategy - Szakács, Alexandru (Frontiers in Earth Science, 2021)
The article discusses the controversial topic of the precursor-based earthquake prediction, based on a personal perspective intending to stir the current still waters of the issue after twenty years have passed since the influential debate on earthquake prediction hosted by Nature in 1999. The article challenges the currently dominant pessimistic view on precursor-based earthquake prediction resting on the "impossibility in principle" paradigm. Instead, it suggests that a concept-based innovative research strategy is the key to obtain significant results, i.e. a possible paradigm shift, in this domain. The basic concept underlying such a possible strategy is the “precursory fingerprint” of individual seismic structures derived from the uniqueness of the structures themselves. The task is to find as many unique fingerprints as possible for different seismic structures worldwide covering all earthquake typologies. To achieve this, a multi-parameter approach involving all possible sensor types (physical, chemical, biological) of the highest available sensitivity, as well as artificial intelligence could be used. The findings would then be extrapolated to other similar structures. One key issue is the emplacement location of the sensor array in privileged “sensitive” Earth-surface sites (such as volcanic conduits) where the signal-to noise ratio is maximized, as suggested in the article. The strategy envisages three stages: experimental, validation and implementation. It inherently could be a costly, multi-disciplinary, international and long-term (i.e. multi-decade) endeavor with no guaranteed success, however less adventurous but socially more significant in comparison to the currently running and well-funded SETI Project.